HIGH DISPERSION OF IRON CATALYST ONTO CARBON NANOFIBER (CNF) AS CATALYST SUPPORT FOR HABER BOSCH PROCESS - ABD WAHAB, NUR WASIMAH (2021)
CNF is usually contaminated with amorphous carbon and metal impurities, chemically inert and insolubility from hydrophobic nature hinders transfer and deposition of catalyst particles like iron. Despite as one of the most active metal catalysts, iron catalyst exhibits low dispersion and low specific surface area. The aim of this research is to improve iron dispersion, iron exposed surface area and nanoparticle size. The goals are achieved by modifying the structure and synthesizing iron (III) nitrate nonahydrate on modified CNF via deposition precipitation method. The developed catalysts were performed in ammonia synthesis to demonstrate Fe/CNF potential application in catalysis. In this study, CNF was modified with concentrated nitric acid (HNO3). The treatment for 2 hours (2-H) was found to obtain clear CNF bundles, lowest amorphous carbon (IA/IG), and highest acid surface oxygen groups of 1.557 mmol/g. Different urea amount was used for the optimization of iron deposition on modified CNF. Results showed that mole ratio of 3:1 (urea: iron) exhibit higher yield of iron loading, homogeneous distribution, and smaller size of 1-9 nm (5wt.%) and 2-13 nm (10 wt.%). Various iron loading was synthesized on modified CNF using mole ratio of 3:1 (urea: iron). Small iron nanoparticle size of 7.42- 42.24 nm, high dispersion of 12.17-27.07% and high iron exposed surface area (64.99-151.739 m2.gcat-1) were obtained. It was found that the number of iron exposed surface area was strongly dependent on iron dispersion and nanoparticle size. Catalyst performance was evaluated, and result shows that high TOF was obtained from 5Fe/2-H which has the highest dispersion, highest exposed iron surface area and smaller size. In conclusion, high dispersion, high loading, and uniform distribution of iron nanoparticles can be achieved by using modified CNF and deposition precipitation method. However, they are also strongly dependent on urea amount as it is related to particle nucleation and the growth of iron precipitate. High dispersion and high number of iron exposed surface area with Fe (211) and Fe (110) crystal faces are suggested in assisting ammonia catalytic activity even though only low concentration was produced from CNF supported monometallic iron catalyst.